2017
DOI: 10.1007/978-3-319-67591-6_4
|View full text |Cite
|
Sign up to set email alerts
|

The Translational Controlled Tumour Protein TCTP: Biological Functions and Regulation

Abstract: The Translational Controlled Tumour Protein TCTP (gene symbol TPT1, also called P21, P23, Q23, fortilin or histamine-releasing factor, HRF) is a highly conserved protein present in essentially all eukaryotic organisms and involved in many fundamental cell biological and disease processes. It was first discovered about 35 years ago, and it took an extended period of time for its multiple functions to be revealed, and even today we do not yet fully understand all the details. Having witnessed most of this histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 236 publications
(405 reference statements)
2
40
0
1
Order By: Relevance
“…Thus, high levels of TCTP and vimentin might act as tumor enhancer for NSCLCs in both smokers and non-smokers (Additional file 1: Table S1). The results were consistent with the report that high TCTP levels were typically associated with advanced tumors and poor patient outcomes of brain tumor, breast cancer, colorectal cancer, hepatocellular carcinoma, neuroblastomas, and ovarian cancer [28].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, high levels of TCTP and vimentin might act as tumor enhancer for NSCLCs in both smokers and non-smokers (Additional file 1: Table S1). The results were consistent with the report that high TCTP levels were typically associated with advanced tumors and poor patient outcomes of brain tumor, breast cancer, colorectal cancer, hepatocellular carcinoma, neuroblastomas, and ovarian cancer [28].…”
Section: Discussionsupporting
confidence: 92%
“…Although TCTP was required for carcinogensinduced EMT, how PM 2.5 and NNK up-regulated TCTP expression remained unclear. Transcriptional regulation of TCTP gene via transcription factor such as CREB, P53, and HIF-1α has been reported [28], however, DNA methylation, the most studied epigenetic regulatory mechanism on transcriptional level, was not yet examined for TCTP. In our experiments, lower level of DNA methylation in TCTP promoter region and the discrepancy between NCI-H23 and Bet1A cells indicated that methylation did not play a key role in TCTP expression in PM 2.5 and NNK induced EMT (Additional file 1: Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor protein translationally controlled 1 is a multifunctional protein implicated in a diverse array of biological processes related to cell growth and tumor development; in addition, elevated TPT1 expression is strongly associated with aggressive tumor biological behavior, metastatic potential and poor prognosis . The PI3K/AKT signaling pathway has been observed in various cancers and can frequently modulate EOC metastasis, angiogenesis and chemoresistance, and corresponding inhibitors targeting this pathway, such as BKM120, GSK2110183 and AZD5363, are currently being evaluated as effective treatment strategies for EOC . Because the PI3K/AKT signaling pathway has been reported as a downstream factor for the maintenance of tumor malignancy by TPT1, we preliminarily proved that the knockdown of TPT1 in TPT1‐AS1‐overexpressing EOC cells could significantly impede tumor cell proliferation and metastasis in vitro and decrease the phosphorylation of PI3K and AKT, which indicated that TPT1‐AS1 might promote EOC tumorigenesis and dissemination through the TPT1/PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 84%
“…It is known as an essential mitotic factor and a promoter of cellular growth interacting with the protein synthesis machinery, and also as a cytoprotective and anti-apopoptic protein (reviewed by [33, 34]). Although best characterised in animals given their high relevance to malignancy and cancer progression, these core functions appear largely conserved in other eukaryotes, including plants, and make TCTPs essential proteins to embryogenesis and early development, organ patterning, regulation of organ size and cellular homeostasis [34]. In Arabidopsis, knock-out mutations of either AtTCP1 or its homologue, AtTCTP2 are lethal [35, 36], as is the case of TCTP loss of function in mice [37] or drosophila [31].…”
Section: Introductionmentioning
confidence: 99%